Experience : culture, cognition, and the common sense - Jones, Caroline A.; Mather, David; Uchill, Rebecca, 1978-; Center for Art, Science & Technology (Massachusetts Institute of Technology) (Cambridge, Mass. : MIT Press, 2016)
Experience offers a reading experience like no other. A heat-sensitive cover by Olafur Eliasson reveals words, colors, and a drawing when touched by human hands. Endpapers designed by Carsten Holler are printed in ink containing carefully calibrated quantities of the synthesized human pheromones estratetraenol and androstadienone, evoking the suggestibility of human desire. The margins and edges of the book are designed by Tauba Auerbach in complementary colors that create a dynamically shifting effect when the book is shifted or closed. When the book is opened, bookmarks cascade from the center, emerging from spider web prints by Tomas Saraceno. Experience produces experience while bringing the concept itself into relief as an object of contemplation. The sensory experience of the book as a physical object resonates with the intellectual experience of the book as a container of ideas. Experience convenes a conversation with artists, musicians, philosophers, anthropologists, historians, and neuroscientists, each of whom explores aspects of sensorial and cultural realms of experience. The texts include new essays written for this volume and classic texts by such figures as William James and Michel Foucault.
Sponsored by the MIT Center for Art, Science & Technology.
boek
Keywords: Experience